Temporary settlements and transient populations. The legacy of Britain‘s prisoner of war camps: 1940–1948 - Hellen, J. Anthony (ERDKUNDE, 1999)
Although prisoner of war camps became a feature of the British landscape between 1942 and 1948, eventually totalling around 1500 camps and hostels and housing over 500,000 men, they have attracted little attention as geographical phenomena. Most of the substantive research on the POW has been undertaken by political and social historians in Britain and Germany. This paper attempts to fill an apparent gap by tracing the development of a complex military settlement system, now largely obliterated by normal forces of change and decay, and by analyzing the policies which led to the location, operation and evolution of the camp sites. Detailed maps of the expanding prison camp system, together with five representative site plans, are presented. Their role in providing involuntary labour at a critical period of post-war recovery, particularly for agriculture, is also examined. Today most of the contemporary camp records have been lost or culled, and the generation responsible for, or confined in them up to 1948, is dying out. Nonetheless, the public and private records, are probably still sufficient to rescue the historical geographies of many of these transient settlements before they become the preserve of military archeologists. This aspect of military geography remains a challenging, if currently neglected, field for future research.